Coherence and divergence in services trade law - Hoffmann, Rhea Tamara; Krajewski, Markus 1969- (Springer International Publishing, 2020)
Markus Krajewski and Rhea Tamara Hoffmann, Introduction -- Panagiotis Delimatsis, Coherence and Divergence in Agreements on Trade in Services: A Drama in Three Acts -- Johanna Jacobsson, Services liberalization by sub-central entities – towards deeper commitments? -- Gabriel Gari, Recent developments on disciplines on domestic regulations affecting trade in services: convergence or divergence? -- Svetlana Yakovleva, Privacy and data protection in the EU- and US-led Post-WTO Free Trade Agreements -- Ines Willemyns, Addressing Digital Services in PTAs: only convergence in the 11th hour? -- Marion Panizzon and Harjodh Singh, Regulatory or Market-driven Coherence of the Movement of Natural Persons across EU and Asian Preferential Trade Agreements -- Mira Burri, Telecommunications and Media Services in Preferential Trade Agreements: Path Dependences Still Matter -- Carlo M. Cantore, "Parallel convergences" in free trade agreements on financial services: Select issues -- Lijun Zhao, Maritime Transport, the WTO, and Regional Trade Agreements: Too Many Cooks? -- Weiwei Zhang, Embracing Global Tax Reform in the General Agreement on Trade in Services?
Keywords: International law; Trade; Commercial law; International economics